Embedded smart camera performance analysis - Kahar, N.F; R.Badlishah, Ahmad; Zulkifli, Hussin; Ahmad Nasir, Che Rosli (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org